Exploration of recycled tires for development of new products - Amorim, Bernardo Nuno Guerra (2018)
It is estimated that, in industrialized societies, over 9 to 10 Kg of tires per habitant are annually discarded and pilled in huge deposits with serious environmental problems associated. It is of maximum importance recycling used tires and developing new applications and new products of recycled tires. In this work, recycled tire granulates, produced by RECIPNEU, are incorporated in polylactic acid (PLA) to prepare polymeric composite formulations to be extruded into a filament for sustainable additive manufacturing of an acoustic panel. The preparation of the formulations involved a first theoretical/modelling study based on the mechanical properties and density to “guide” the establishment of the amount of recycled tire granulates to be included. Then, some formulations containing rubber percentages from 10 to 60 wt.% were prepared using a Brabender mixer. Then, upon extrusion of the filaments with the different formulations, it was verified that the composite mixture containing 20 wt.% of rubber was the one presenting a higher degree of homogeneity despite its brittleness. A plasticizer, namely glycerol, was added to improve the filament flexibility and allow its rolling. A printable filament was obtained, and small prototypes of acoustic type panels were printed. Acoustic properties were determined in the laboratory of Professor Doctor Luís Godinho, director of the Department of Civil Engineering of the University of Coimbra, using the Wave Impedance Tube method, and were compared with similar shaped printed pure PLA. Resuming, recycling tires waste were successfully incorporated in PLA and the polymeric composites could be extruded in filament form that can be used as a sustainable material for additive manufacturing. The acoustic performance of the printed panels, tested by Wave Impedance Tube method, revealed an inferior performance when compared with standard mineral wool sample, being necessary to perform more studies in this field